Pengaruh Likuiditas, Opini Audit, Ukuran Perusahaan dan Profitabilitas tePengaruh Likuiditas, Opini Audit, Ukuran Perusahaan dan Profitabilitas Terhadap Ketepatan Waktu pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2011 -2013 - Hantono - (Jurnal Wira Ekonomi Mikroskil, 2015)
This study aims to verify and analyze the impact of liquidity, audit opinions, company size and profitability of the companies listed in Indonesia Stock Exchange in 2011-2013.Populasi in this study were 145 companies listed in Indonesia Stock Exchange 2011-2013. Of the 145 listed companies, 134 companies selected samples using purposive sampling. The data used in this research is secondary data, by collecting the required information from idx form of financial statements in 2011-2013.Metode used to analyze the relationship between independent variables and the dependent variable is a multiple regression analysis, and test asumsi. The results of this study indicate that simultaneous independent variables; liquidity, audit opinion, the size of the company and profitability with the F test, jointly affect the timeliness. Partial results with the t test, variable liquidity, audit opinion, the size and profitability of the timeliness